A case of stillbirth caused by rupture of an intrahepatic hemangioma and the wish for litigation - U. Indraccolo; S.R. Indraccolo; P. Greco; P. Fedeli (IMR Press, 2020)
A very uncommon case of an intrahepatic hemangioma rupture as a cause of a stillborn baby is presented. It seems that the event could not be detected. However, the idea of litigation pushed parents to ascertain hypothetical liability of physicians 10 years after the stillbirth. The reason that parents do not comprehend that such a rare event could occur and opt for litigation was investigated. The conclusion seems that some patients' beliefs do not agree with physician counseling and cause the failure of the medical goals for the best care; thus, an improvement in counseling would still be ineffective. Rather, lowering parents' expectations from medical assessments and care seems the right way to reduce the incidence of litigation.